Analysis of social and environmental aspects the margin of the Maranguapinho river between the Bonsucesso and Granja Portugal (Fortaleza, Ceará) - Santos, Luan de Paula dos; Araújo, Henrique Eder Cavalcante (Geosaberes, 2019)
Approximately 48 km long, the Maranguapinho River is one of the main rivers in the Metropolitan Region of Fortaleza, with some 9,422 families living in areas at risk of occupying land parcels unfit for human habitation. In this perspective, we intend to analyze the land use and occupation relations between the Bonsucesso and Granja Portugal districts based on the field analysis, vector and matrix data, and previous studies. It is considered that the anthropic action is the main modifier of the landscape causing also an environmental imbalance that discharacterizes the area of ​​study. As a counterpart in this situation, the public power seeks to revitalize the region, so that it can be recovered in both the environmental and urban / social aspects.